Possible role of horizontal gene transfer in the colonization of sea ice by algae. - James A Raymond (Public Library of Science (PLoS), 2012)
Diatoms and other algae not only survive, but thrive in sea ice. Among sea ice diatoms, all species examined so far produce ice-binding proteins (IBPs), whereas no such proteins are found in non-ice-associated diatoms, which strongly suggests that IBPs are essential for survival in ice. The restricted occurrence also raises the question of how the IBP genes were acquired. Proteins with similar sequences and ice-binding activities are produced by ice-associated bacteria, and so it has previously been speculated that the genes were acquired by horizontal transfer (HGT) from bacteria. Here we report several new IBP sequences from three types of ice algae, which together with previously determined sequences reveal a phylogeny that is completely incongruent with algal phylogeny, and that can be most easily explained by HGT. HGT is also supported by the finding that the closest matches to the algal IBP genes are all bacterial genes and that the algal IBP genes lack introns. We also describe a highly freeze-tolerant bacterium from the bottom layer of Antarctic sea ice that produces an IBP with 47% amino acid identity to a diatom IBP from the same layer, demonstrating at least an opportunity for gene transfer. Together, these results suggest that the success of diatoms and other algae in sea ice can be at least partly attributed to their acquisition of prokaryotic IBP genes.